Carbonic anhydrases in development: morphological observations and gene expression profiling in sea urchin embryos exposed to acetazolamide. Issue 1 (4th January 2023) - Zito, Francesca; Bonaventura, Rosa; Costa, Caterina; Russo, Roberta
Abstract : Abstract : Carbonic anhydrases (CANs) are conserved metalloenzymes catalysing the reversible hydration of carbon dioxide into protons and bicarbonate, with important roles in cells physiology. Some CAN-coding genes were found in sea urchin genome, although only one involved in embryonic skeletogenesis was described in Paracentrotus lividus . Here, we investigated gene expression patterns of P. lividus embryos cultured in the presence of acetazolamide (AZ), a CAN inhibitor, to combine morphological defects with their molecular underpinning. CAN inhibition blocked skeletogenesis, affected the spatial/temporal expression of some biomineralization-related genes, inhibited embryos swimming. A comparative analysis on the expression of 127 genes in control and 3 h/24 h AZ-treated embryos, using NanoString technology, showed the differential expression of genes encoding for structural/regulatory proteins, with different embryonic roles: biomineralization, transcriptional regulation, signalling, development and defence response. The study of the differentially expressed genes and the signalling pathways affected, besides in silico analyses and a speculative 'interactomic model', leads to predicting the presence of various CAN isoforms, possibly involved in different physiological processes/activities in sea urchin embryo, and their potential target genes/proteins. Our findings provide new valuable molecular data for further studies in several biological fields: developmental biology (biomineralization, axes patterning), cell differentiation (neural development) and drug toxicology (AZ effects on embryos/tissues).